Exploring Teacher's Perceptions about Digital Story Telling Assessments Method Case of Online Master Didactics University of M’sila - Sadoun Souad; Khemliche Sarra (UNIVERSITY OF MOHAMED BOUDIAF- M’SILA, 2025)
Abstract This dissertation explores the perceptions of university teachers regarding the use of digital storytelling (DST) as an alternative assessment method in online education, focusing on Master in Didactics of Applied Languages – Online Programme at the University of M’sila. The research investigates both the perceived benefits and challenges of implementing DST in assessment practices. Using a mixed-methods design, data were collected through a structured online questionnaire. Results show strong agreement on DST’s benefits in enhancing student engagement, creativity, and digital skills. However, teachers noted challenges such as technical barriers, lack of training, and time constraints. Qualitative findings highlight that its successful integration requires institutional support, teacher training, and access to digital resources. The study concludes that DST can enhance assessment practices if supported by adequate training and infrastructure.
Keywords: Key words: Digital Storytelling (DST); Alternative Assessment; Teacher Perceptions; Master in Didactics of Applied Languages; University of Mohammed Boudiaf M’sila; Online Education.